TO PLAY AND THE ENJOYMENT IN SCHOOL PHYSICAL EDUCATION CLASSES (Fiep Bulletin - online, 2013)
The reason for accomplishment this studying was verify scientifically, through Literature revision , the importance of to play and the enjoyment in school Physical Education classes. It's through enjoyment that enjoy, creativeness, enjoyment and the imaginary to take place in kid's life. In games, the imaginary formation will be developed, permitting kid to play in any one society where she lives. Therefore, the enjoyment and to play ought to be add in Physical Education class, because they have grand significance for the integral development kid.
Keywords: enjoyment; to play; education; Physical Education; game